'Exempted soldiers' in the 'New Sensitivity Military': public opinion among Jewish Israelis concerning selective conscientious objection (military refusal) and the Military Recruitment Model. Issue 1 (2nd January 2019) - Lebel, Udi; Orkibi, Eithan
Abstract: In recent decades (the ‗post-heroic' condition) - threats of widespread selective conscientious objection have become a political tool to advance opposing political agendas in Israel. This article examines attitudes amongst the Israeli public concerning the legitimacy of demands that different groups of soldiers be exempted from military operations to which they are ideologically opposed (such as serving in the occupied territories or, conversely, participating in evacuation of settlements). The results point to a multi-cultural model embracing diversity management not as a neo-liberal ideal but rather as a strategy for co-option, containment and inclusion, with a view to preserving the "people's army" model.